2020
DOI: 10.1101/2020.03.25.008185
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Novel Method for Calculating Beta Band Burst Durations in Parkinson’s Disease Using a Physiological Baseline

Abstract: Parkinson's disease, Deep Brain Stimulation HighlightsA novel method for measuring variability in subthalamic local field potential oscillations in Parkinson's disease using a physiological baseline of power.Modeling normal brain activity using a physiological 1/f spectrum.Burst durations depend on choice of bandwidth and center frequency.Defining an inert frequency band whose mean burst duration overlap the physiological 1/f spectrum, from which the baseline was determined.Burst durations progressively shorte… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 39 publications
(67 reference statements)
0
21
0
Order By: Relevance
“…The temporal dynamics of beta band power (termed beta bursts) have been associated with clinical assessments of disease severity and with kinematic measures of bradykinesia, gait impairment, and FOG (Tinkhauser et al, 2017b ; Anidi et al, 2018 ). There is a similar dose dependency between DBS intensity and beta burst duration both during rest and movement: increasing intensities of STN DBS were associated with shorter mean beta band durations and improved bradykinesia (Anderson et al, 2020 ). This dose-dependency of beta bursts suggests that a similar dual-threshold control policy in bidirectional DBCIs that monitors prolonged beta burst durations, as opposed to beta power specifically, could keep the DBS intensity within a therapeutic window.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The temporal dynamics of beta band power (termed beta bursts) have been associated with clinical assessments of disease severity and with kinematic measures of bradykinesia, gait impairment, and FOG (Tinkhauser et al, 2017b ; Anidi et al, 2018 ). There is a similar dose dependency between DBS intensity and beta burst duration both during rest and movement: increasing intensities of STN DBS were associated with shorter mean beta band durations and improved bradykinesia (Anderson et al, 2020 ). This dose-dependency of beta bursts suggests that a similar dual-threshold control policy in bidirectional DBCIs that monitors prolonged beta burst durations, as opposed to beta power specifically, could keep the DBS intensity within a therapeutic window.…”
Section: Introductionmentioning
confidence: 95%
“…The benchtop system played back previously recorded neural data and recorded output stimulation from the developed system. We used STN beta burst durations as the neural inputs and developed a novel faster time scale single threshold control policy algorithm that only increased stimulation intensity after the burst duration exceeded the inferred normal duration from simulated 1/f data, red bars in the left-hand panel in Figure 2 (Anderson et al, 2020 ). The benchtop system successfully adjusted stimulation in real-time in response to prolonged beta burst durations and demonstrated the feasibility of the algorithm by responding to pre-recorded STN data from an individual with PD (Petrucci et al, 2020a ).…”
Section: Introductionmentioning
confidence: 99%
“…Parkinson's disease is a progressive neurological disease, whose severity worsens even on optimal doses of medication. [1][2][3] Recordings of local field potentials (LFPs) in the subthalamic nucleus (STN) have revealed exaggerated neuronal oscillations and synchrony in the beta frequency band (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), known as the beta oscillopathy, which is a marker of the pathophysiology of Parkinson's disease. [4][5][6][7] Beta power has been linked to motor impairment and longer duration of fluctuations of beta power (bursts) are associated with increased motor and gait disablity.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Lofredi et al demonstrated that the duration of low beta (13-20 Hz) bursts in the pathological range predicted the degree of the sequence effect in limb movement [33]. We demonstrated that STN DBS shortened resting state beta band burst durations in a dose-dependent manner [48] and that both 60 Hz and 140 Hz DBS shortened prolonged beta burst durations in people with PD and FOG, while improving their FOG [49]. This suggests that one mechanism for the therapeutic effect of DBS on the sequence effect may be in its ability to attenuate pathological beta burst durations.…”
Section: Discussionmentioning
confidence: 67%